Towards a design methodology for specialized immersive training utilizing virtual reality, serious games, biofeedback, and ux design - Batista, Huoston Rodrigues (2021)
Police forces play a significant role due to the inherent nature of their activities, since these professionals are often exposed to a variety of acute stressful and life-threatening situations. Such situations demand, besides quick decisions, correct judgments by these professionals, which justifies constant training in technical, operational, and psychological aspects. However, police training is expensive, involves risks, has little flexibility of scenarios, and in many cases, besides being insufficient, it is also inefficient. This thesis aimed to propose and validate a method to guide the development of Virtual Reality simulators that combine Biofeedback and Serious Games applied to the specialized training of security professionals and law enforcement agents and that considers the User Experience as the predominant factor. This method originated in the practice and validation of the development of a Virtual Reality simulator prototype, whose sole purpose was to generate knowledge to support the proposition of the referred method. Both the proposed method and the prototype were based on the Design Science Research methodology. This method was submitted to three cycles of evaluation, two with specialists and a third that consisted of a wider evaluation through a survey with 141 professionals and academics from eleven countries from several areas of expertise that this research tangents, such as Software Development, User Experience, Education, Games, and Industry 4.0. After analyzing the survey responses, it was possible to identify different levels of relevance of the 31 activities in each of the 7 cycles, determined by the number of activities defined as very relevant or extremely relevant by the respondents. This made possible to generate a fourth and final version that took into consideration different reflections from the validation performed by professionals and academics. The final version of the method is composed of Phase/Cycle 1 - Definition of the general objectives of the simulator phase (4 activities), Phase/Cycle 2 - Research cycle (3 activities), Phase/Cycle 3 - Planning cycle (5 activities), Phase/Cycle 4 - Design cycle (8 activities), Phase/Cycle 5 - Development cycle (VR) (5 activities), Phase/Cycle 6 - Development cycle (Biofeedback) (3 activities), and, finally, Phase/Cycle 7 - Demonstration and evaluation cycle (3 activities). It was identified that the activities related to User Experience had, in general, excellent ratings from the consulted respondents, while the activities related to Serious Games and Biofeedback were not considered to have the same level of relevance as the activities related to User Experience. However, none of the activities had such low relevance ratings as to suggest their exclusion from the method. Accordingly, the final version of the validated method indicated all thirty-one activities distributed in each of its seven stages, duly labeled as 'mandatory', 'recommended', or 'optional'. It is concluded that the method is sufficiently comprehensive, robust and flexible to cover different specificities of various contexts for the development of Virtual Reality solutions applied to the training of professionals in stressful situations.